Tool path active design for tooth modification of face-hobbed spiral bevel gears. (September 2020) - Guo, Wenchao; Mao, Shimin; Yang, Yu
Abstract: An advanced design and manufacturing method called tool path active design for face-hobbed spiral bevel gears is mainly discussed in this paper. The method bases on the forming mechanism of extended epicycloids and utilizes an integrated cutter head without tilting, meanwhile, all its controlled parameters can be directly calculated according to the given meshing performances and modified conditions. Starting with the cutting principle of face-hobbing method, a tooth flank mending plan of altering tool path is developed, which detailed expressions are also given in functions. Then, the meshing performances which are used to determine the modification parameters are introduced and their formulas are also derived. Finally, the proposed method is validated by a numerical example of tooth contact analysis for a face-bobbed hypoid gear pair. As a further explanation, a numerical example of tooth contact analysis is done to validate the feasibility of the proposed method.